Factors Affecting Divorce During The Covid-19 Pandemic Period in Bukittinggi: Faktor-faktor yang Mempengaruhi Perceraian Selama Masa Pandemi Covid-19 Di Kota Bukittinggi - Dalvi , Ismiranda; Hermaleni, Tesi (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to describe and conclude the factors causing the divorce of married couples in Bukittinggi City. This type of research is qualitative research. The research location was the Bukittinggi Religious Court Office and the research subjects were individuals who experienced divorce during the pandemic and handled a divorce at the Bukittinggi Religious Court Office. The results of this research show that the causes of divorces in the City of Bukittinggi are caused by internal and external factors. From the results of interviews with research subjects, internal factors, such as economic problems, domestic violence and continuous disputes and arguments. Meanwhile, the external factor is infidelity. Of the four factors obtained by researchers through interviews with subjects, infidelity and disputes and arguments are the factors that most often cause couples to decide to divorce, followed by economic factors, and the last one is domestic violence.